The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1176/appi.ajp.162.4.732
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Fluctuation in Eating Disorders: Correlates of Diagnostic Crossover

Abstract: Low self-directedness may be associated with diagnostic instability in general, whereas other specific factors are related to the direction of diagnostic crossover. These results indicate that personality and family characteristics may influence the course of eating disorders and may be informative for planning interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
200
3
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 261 publications
(224 citation statements)
references
References 62 publications
14
200
3
2
Order By: Relevance
“…This is in line with the findings from other studies which reported relapses to bulimic symptoms in both types of AN and in BN. 4,11 Bulik et al 12 concluded from several studies that a large proportion of AN patients later developed BN with the percentage of patients with BN to be increasing with the follow-up interval. Tozzi et al, 11 assessing diagnostic crossover retrospectively in a large sample, found 27% of BN patients shifting to AN.…”
Section: Resultsmentioning
confidence: 99%
“…This is in line with the findings from other studies which reported relapses to bulimic symptoms in both types of AN and in BN. 4,11 Bulik et al 12 concluded from several studies that a large proportion of AN patients later developed BN with the percentage of patients with BN to be increasing with the follow-up interval. Tozzi et al, 11 assessing diagnostic crossover retrospectively in a large sample, found 27% of BN patients shifting to AN.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies on AN have used survival analysis to examine events such as mortality, [67][68][69] relapse, 34,68,70 long-term recovery, 34,36 premature termination of treatment, 71 and symptom crossover. 72 In survival analysis, survival time is made up of two principal components: the follow-up time from a defined starting point and the occurrence of a defined event. 73 In this investigation, LOS starting at admission and ending at discharge comprised the time component and participants' status of meeting the outcome criteria at discharge signaled the event occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…16 Several prospective studies of clinical samples found that many participants with AN develop bulimic symptoms within the first 5 years of their disorder. 4,17 Fichter and Quadflieg found that 10% of those with AN developed BN by 2-12 year follow-up. Furthermore, consistent with other prospective studies (e.g., Refs.…”
Section: Long-term Stability Of Eating Disorder Diagnoses (Fichter Andmentioning
confidence: 99%